The phase separation underlying the pyrenoid-based microalgal Rubisco supercharger. Issue 1 (December 2018) - Wunder, Tobias; Cheng, Steven; Lai, Soak-Kuan; Li, Hoi-Yeung; Mueller-Cajar, Oliver
Abstract The slow and promiscuous properties of the CO2 -fixing enzyme Rubisco constrain photosynthetic efficiency and have prompted the evolution of powerful CO2 concentrating mechanisms (CCMs). In eukaryotic microalgae a key strategy involves sequestration of the enzyme in the pyrenoid, a liquid non-membranous compartment of the chloroplast stroma. Here we show using pure components that two proteins, Rubisco and the linker protein Essential Pyrenoid Component 1 (EPYC1), are both necessary and sufficient to phase separate and form liquid droplets. The phase-separated Rubisco is functional. Droplet composition is dynamic and components rapidly exchange with the bulk solution. Heterologous and chimeric Rubiscos exhibit variability in their tendency to demix with EPYC1. The ability to dissect aspects of pyrenoid biochemistry in vitro will permit us to inform and guide synthetic biology ambitions aiming to engineer microalgal CCMs into crop plants. The microalgal pyrenoid has been reported to behave as a phase-separated liquid compartment. Here the authors demonstrate that the CO2-fixing enzyme Rubisco and the linker protein EPYC1 are necessary and sufficient to bring about a liquid-liquid phase separation that recapitulates the pyrenoid's liquid-like behavior.